2021
DOI: 10.1177/87551233211043887
|View full text |Cite
|
Sign up to set email alerts
|

Theme and Variations on a Virtue: Humility as a Multidimensional Construct for Musicians and Music Educators

Abstract: Humility is an important social virtue for musicians as they expose their own egos in the pursuit of artistic self-expression. Research findings have confirmed that humility is an important virtue of strength that lends itself meaningfully to prosocial and ethical interactions among musicians and music educators. In this article, I synthesize research on various forms of humility that emerge from unique social situations in which musicians and music educators might find themselves. In actively seeking to devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Several accounts of egotism 2 have been offered by psychologists and philosophers, but they may not necessarily correspond to the specific ways in which it manifests in artistic spaces. Given that music participation simultaneously demands a heightened sense of self-confidence, along with the courageous expression of the self, one's social presentation may be distinctive to their artistic pursuits (Coppola, 2022, Eustis, 2005. Tanesini (2021) differentiates between four types of egotism that collectively comprise the vices of superiority.…”
Section: Framing Egotismmentioning
confidence: 99%
See 1 more Smart Citation
“…Several accounts of egotism 2 have been offered by psychologists and philosophers, but they may not necessarily correspond to the specific ways in which it manifests in artistic spaces. Given that music participation simultaneously demands a heightened sense of self-confidence, along with the courageous expression of the self, one's social presentation may be distinctive to their artistic pursuits (Coppola, 2022, Eustis, 2005. Tanesini (2021) differentiates between four types of egotism that collectively comprise the vices of superiority.…”
Section: Framing Egotismmentioning
confidence: 99%
“…Tanesini (2021) suggested that a disproportionate focus on virtue-oriented perspectives, largely stemming from the field of positive psychology, has yielded an inadequate understanding of the vices that hinder the pursuit of virtue in social life. Accordingly, while the virtue of humility has been recently examined in music (e.g., Coppola, 2019Coppola, , 2020Coppola, , 2021Coppola, , 2022, the vices of egotism 1 compel scholarly investigation as well. In this study, I shed light on how egotism, conceived as a cluster of pernicious social vices, manifests in music settings.…”
mentioning
confidence: 99%